Children's hair cortisol as a biomarker of stress at school entry. (November 2013) - Groeneveld, Marleen G.; Vermeer, Harriet J.; Linting, Mariëlle; Noppe, Gerard; van Rossum, Elisabeth F. C.; van IJzendoorn, Marinus H.
Abstract Quantification of cortisol in scalp hair seems a promising measurement for long-term cortisol levels, and thereby a biomarker for stress. We examined hair cortisol concentrations (HCC) in children when first entering elementary school. Participants were 42 children (45% boys) with a mean age of 4.2 years (SD = 0.42 months). Hair samples (≥5 cm) were collected 2 months after school entry. Hair analysis was conducted using two 2-cm long segments, reflecting the first 2 months of school attendance (the scalp-near segment) and 2 months prior to school entry. HCC were higher after school entry than before, especially for fearful children. Alterations in HCC were not moderated by experience in group daycare before school entry. Thus, HCC suggest that starting elementary school is accompanied by increased stress hormone levels in young (in particular fearful) children.